The authenticity of souvenirs: examples from Taiwan - Wall, Geoffrey (Frontiers in Sustainable Tourism, 2024)
The purpose of this study is to demonstrate that authenticity is a complicated and imprecise concept. Using autoethnography as an approach to the study and, in particular, a consideration of the meanings of aboriginal souvenirs originating in Taiwan that are in the authors' possession, it is shown that these objects do not fit snuggly into typical classifications that have been proposed to address authenticity. Authenticity is a concept that can hide issues of power and powerlessness. It is suggested that authentication, who says something is authentic and why they do so, is important as it facilitates consideration of access to power.